2000
DOI: 10.1161/01.atv.20.12.2657
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-1 and Interleukin-6 Gene Promoter Polymorphisms Are Determinants of Asymptomatic Carotid Artery Atherosclerosis

Abstract: Abstract-The functional 5A/6A polymorphism of the stromelysin-1 promoter has been implicated as a potential genetic marker for the progression of angiographically determined atherosclerosis in patients with coronary artery disease. Recently, a novel interleukin-6 (IL-6) gene functional G/C polymorphism at Ϫ174 in the promoter has also been reported. In this study, we analyzed the relation of these two polymorphisms with carotid artery atherosclerosis in 109 randomly selected, middle-aged men without exercise-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
109
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(128 citation statements)
references
References 49 publications
14
109
2
3
Order By: Relevance
“…[40][41][42] A guanine to cytosine (G→C) substitution at nucleotide -174 of the IL-6 promoter has been reported to affect gene transcription and has been associated with a number of conditions in which inflammation is considered to play a role. 21,43,44 Allelic associations with severe sepsis were evaluated previously for 159 of the 228 patients described in this report. 10 The present study included patients with ≥15% TBSA burns, compared to patients with ≥20% burns in the previous analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] A guanine to cytosine (G→C) substitution at nucleotide -174 of the IL-6 promoter has been reported to affect gene transcription and has been associated with a number of conditions in which inflammation is considered to play a role. 21,43,44 Allelic associations with severe sepsis were evaluated previously for 159 of the 228 patients described in this report. 10 The present study included patients with ≥15% TBSA burns, compared to patients with ≥20% burns in the previous analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-6 activity and plasma levels have been associated with several hypertensioninduced disturbances, in particular atherosclerosis. 24 Immunohistochemical studies of the human arterial atherosclerotic wall have demonstrated that IL-6 is expressed in the cellular and extracellular deposits in the connective tissue matrix and that atherosclerotic plaques have high levels of IL-6. 25 Studies in ApoE-knockout mice, that spontaneously develop systemic atherosclerosis, also show elevated levels of IL-6 mRNA in the plaque area compared with normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Аналіз одержаних даних [74,75] виявив, що особи із 6A-алелем мали нижчу експресію MMP-3, ніж ті, у яких був 5А-алель [50], більші розміри атероми і навіть частіший рестеноз після ангіопластики. 6А-алель асоційований зі зниженням експресії ММР-3 і прискореним розвитком атеросклерозу через підвищення вмісту колагену в позаклітинному матриксі артерій.…”
Section: поліморфізм ммр-3unclassified